Myocardial remodeling and dysfunction are induced by chronic food restriction in spontaneously hypertensive rats - Okoshi, Marina Politi [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Dal Pai-Silva, Maeli; Gut, Ana Lúcia [UNESP]; Padovani, Carlos Roberto [UNESP]; Dal Pai, Vitalino; Cicogna, Antonio Carlos [UNESP] (Elsevier B.V., 2006)
Several studies have shown alterations in hearts from animals subjected to food restriction (FR). However, few experiments in hearts evaluating pressure overload have been reported. We examined the effects of chronic FR on myocardial function and morphology in spontaneously hypertensive rats (SHR). Sixty-day-old SHR were fed a control (C) or a restricted diet (daily intake reduced to 50% of amount of food consumed by the control group) for 90 days. Myocardial performance was studied in isolated left ventricular (LV) papillary muscle. Food restriction decreased body weight and LV weight; LV weight/body-weight ratio was lower in the food-restricted group (SHR-C, 2.84 +/- 0.21 mg/g; SHR-FR, 2.56 +/- 0.24 mg/g; P <.05). Food restriction did not change arterial systolic blood pressure. Myocyte surface area was lower in the food-restricted group (P <.01). Food restriction induced myocardial ultrastructural alterations including reduced sarcoplasm content, reduced and disorganized myofilaments, disorganized Z line, dilated sarcoplasmic reticulum, and deep infoldings of plasma membrane. Myocardial hydroxyproline concentration was increased in the restricted rats. Peak developed tension (P <.05) and maximum rate of tension development (P <.01) were decreased in the SHR-FR group. In conclusion, myocardium of SHR subjected to chronic FR presents attenuation of hypertrophy development, ultrastructural changes, increased collagen content, and systolic dysfunction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: SHR; papillary muscle; myocardial ultrastructure; myocardial function; cardiac hypertrophy; undernutrition; rat